2013
DOI: 10.1007/s12253-013-9691-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Blood Dendritic Cells in Colorectal Cancer Patients During the Course of Disease

Abstract: Colorectal cancer is a malignancy with poor prognosis that might be associated with defective immune function. The aim of the present study was to investigate circulating dendritic cells in colorectal cancer patients, in order to contribute to elucidate tumor-escape mechanisms and to point out a possible correlation with the clinical condition of the disease. Therefore, we enumerated ex vivo myeloid and plasmacytoid dendritic cells, through multicolor flow cytometry, in 26 colorectal patients and 33 healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…The relevance of ILT3 in cancer patients is supported by results from the literature 14,37,38 and therefore further investigation of its mode of action should be performed. Nonetheless, it is debatable whether ILT3 on its own would determine the immunosuppressive status of MDSCs; rather, the sum of all immunosuppressive mechanisms and their relative contribution to the activity of MDSC will probably determine the extent of its unfavorable effects in cancer patients.…”
Section: Ilt3mentioning
confidence: 88%
See 1 more Smart Citation
“…The relevance of ILT3 in cancer patients is supported by results from the literature 14,37,38 and therefore further investigation of its mode of action should be performed. Nonetheless, it is debatable whether ILT3 on its own would determine the immunosuppressive status of MDSCs; rather, the sum of all immunosuppressive mechanisms and their relative contribution to the activity of MDSC will probably determine the extent of its unfavorable effects in cancer patients.…”
Section: Ilt3mentioning
confidence: 88%
“…10 An important mediator of the induction of immune tolerance is immunoglobulin-like transcript (ILT) 3 (also known as LILRB4, CD85k, or LIR-5), which is expressed on monocytes and antigen-presenting cells (APCs) such as macrophages and dendritic cells (DCs). 11,12 ILT3 expression marks tolerogenic DCs and has been reported to be elevated in APCs of cancer patients 13,14 and decreased in autoimmune diseases. 15,16 ILT3 is believed to signal via its immunoreceptor tyrosine-based inhibitory motifs (ITIMs).…”
Section: Introductionmentioning
confidence: 99%
“…The studies evaluating levels of circulating cDCs and pDCs in CRC patients have resulted in conflicting data. One report showed that the levels of pDCs, but not cDCs, in blood were reduced in CRC patients (138). In contrast, another study showed that levels of both circulating cDCs and pDCs were reduced in CRC patients (139).…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
“…NSCLC patients with an increased LILRB4 high population had a shorter median survival than patients with a decreased LILRB4 high subset [55]. LILRB4 expression on conventional DC and pDCs was increased in colorectal cancer patients when compared to healthy controls [56]. While LILRB4 is down-regulated following DC activation [57], its expression is up-regulated on tolerogenic DCs, leading to the induction of Treg cells [58].…”
Section: The Role Of Lilrb-expressing Myeloid Cells In the Tumor Micrmentioning
confidence: 99%